The Effect of Scarcity, Serendipity and Website Quality on The Urge to Buy Impulsively and Its Implication on Online Impulsive Buying of Consumer in Manado City - Nova Christian Mamuaya; Ramon Arthur Ferry Tumiwa (AIBPM Publisher, 2018)
The purpose of this research is to analyze the effect of scarcity, serendipity and website quality on the urge to buy impulsively as well as the effect of scarcity, serendipity, website quality and the urge to buy impulsively on online impulse buying. The samples are using 100 people of Manado City that did online shopping and impulsively with convenience sampling; instrument questionnaire with Likert Scale and structural equation modeling analysis technique with SmartPLS 3.0. The result of this research shows that scarcity, serendipity and website quality significantly affected on the urge to buy impulsively and scarcity, serendipity, website quality and urge to buy impulsively significantly affected on online impulse buying. Keywords: scarcity, serendipity, website quality, urge to buy impulsively, online impulse buying, Manado